Analisis Dinamika Atmosfer Saat Peristiwa Siklon Tropis Paddy di Pulau Jawa - Aslam, Fadhil Muhammad (UNIVERSITAS INDRAPRASTA PGRI, 2024)
Java Island is the most densely populated island in Indonesia. Consequently, Java Island is also prone to atmospheric disturbances that affect the activities of its inhabitants. One such event was Tropical Cyclone Paddy, which occurred from November 22 to 24, 2021. The aim of this study is to understand and delve into the analysis of atmospheric dynamics during the Tropical Cyclone Paddy event, which subsequently impacts the lives and activities of the people on Java Island. This study utilizes data from various meteorological parameters such as rainfall, zonal and meridional winds, sea surface temperature (SST), humidity, and pressure collected from several sources, namely: Himawari-8 Satellite, GsMap, ECMWF Era 5 hourly data on pressure levels, and NOAA. The research examines the dynamics of sea surface temperature (SST) anomalies, wind patterns, lower-level moisture transport (LLMT), divergence, surface pressure, and rainfall during the Tropical Cyclone Paddy event. Software such as GrADS 2.2 and Python were used for spatial analysis. The analysis indicates that high SST anomalies, convergence, and high LLMT contributed to the formation of convective clouds, ultimately resulting in high rainfall in the southern regions of Java affected by the cyclone. Over time, there was a decline in these phenomena, marked by a decrease in pressure, wind speed, and rainfall, leading to the normalization of weather conditions in Java Island post-cyclone.